Electrochemical Oxidation of Organotrifluoroborate Compounds. Issue 12 (5th October 2016) - Suzuki, Junji; Tanigawa, Masahiro; Inagi, Shinsuke; Fuchigami, Toshio
Abstract: Electrochemical analyses of various organotrifluoroborates, and the corresponding boronic acids and esters, were comparatively studied by using cyclic voltammetry. The organotrifluoroborates were found to have much lower oxidation potentials compared with the latter two types of compounds. We also found a pronounced β‐effect for allyltrifluoroborate, which was indicated by both experimental and theoretical aspects. Such a β‐effect is similar to that of allyltrimethylsilane. Anodic oxidation of n ‐decyltrifluoroborate at a platinum anode gave a radical coupling product in moderate yield, eliminating a boryl moiety. Anodic acetoxylation of phenethyl‐, aryl‐, and styryltrifluoroborates was also successfully carried out at a graphite anode in NaOAc/AcOH to provide the acetoxylated products in good to moderate yields although a large excess of electricity was required. Abstract : Organotrifluoroborates electrolysis : Electrochemical analyses of various organotrifluoroborates are performed to show their lower oxidation potentials compared with corresponding boronic acids and esters. A pronounced β‐effect for allyltrifluoroborate is found, as indicated by experimental and theoretical aspects. Anodic acetoxylation of phenethyl‐, aryl‐, and styryltrifluoroborates is successfully carried out in NaOAc/AcOH to provide the acetoxylated products in good‐to‐moderate yields.